PENGUATAN PENDIDIKAN KARAKTER (PPK) BERBASIS KELAS PADA KELAS B1 TK NEGERI KELURAHAN SETAPUK BESAR - Zahrati, Adibah; R, Marmawi; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research aims to describe class-based Strengthening Character Education (PPK) activities for children aged 5-6 years in class B1 of the State Kindergarten, Setapuk Besar Village in terms of planning, implementation and assessment. The research method used is a qualitative descriptive research method. The subjects in this research were class B1 teacher and the Head of the Setapuk Besar District State Kindergarten. Data collection techniques are through observation, interviews and documentation studies with the instruments used, namely observation, interview and documentation guide sheets. Data analysis was carried out using the Miles and Huberman analysis model which consists of data collection, data reduction, data presentation, and drawing conclusions/verification. The results of the research show that the Setapuk Besar Subdistrict State Kindergarten implemented class-based Character Education Strengthening (PPK) with the following steps: (1) PPK planning was carried out through learning planning by integrating PPK values in preparing the RPPH, (2) PPK implementation was carried out integrated in learning activities by following the RPPH integrated with the PPK values that have been prepared, and (3) the PPK assessment is carried out integrated in the learning assessment